2012
DOI: 10.1002/pmic.201100496
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Taenia solium metacestode excretion–secretion proteins

Abstract: The metacestode larval stage of Taenia solium is the causal agent of a zoonotic disease called cysticercosis. The disease has an important impact on pork trade (due to porcine cysticercosis) and public health (due to human neurocysticercosis). In order to improve the current diagnostic tools and to get a better understanding of the interaction between T. solium metacestodes and their host, there is a need for more information about the proteins that are released by the parasite. In this study, we used protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 57 publications
2
31
0
1
Order By: Relevance
“…This revealed that a major 120 kDa complex was composed of precursor sub-units of 14 and 18 kDa that had a potential as biomarkers for differentiation of stages of neurocysticercosis. A later investigation, using LC and MS/MS of excretion-secretion proteins from T. solium metacestode from pigs has revealed a more extensive group of proteins [103]. A total of 76 proteins were identified, 27 of which were already identified as T. solium protein and a further 32 likely to be parasite derived but based on sequences from other helminths.…”
Section: Parasite Diseasesmentioning
confidence: 99%
“…This revealed that a major 120 kDa complex was composed of precursor sub-units of 14 and 18 kDa that had a potential as biomarkers for differentiation of stages of neurocysticercosis. A later investigation, using LC and MS/MS of excretion-secretion proteins from T. solium metacestode from pigs has revealed a more extensive group of proteins [103]. A total of 76 proteins were identified, 27 of which were already identified as T. solium protein and a further 32 likely to be parasite derived but based on sequences from other helminths.…”
Section: Parasite Diseasesmentioning
confidence: 99%
“…The groups were further organized by Gene Ontology annotation information on biological process and molecular function. A total of 48 protein groups are labelled with an asterisk, indicating that they were also identified in the previous study (Additional file 2) [6]. For brevity, Table 1 shows only the 58 newly identified protein groups.…”
Section: Resultsmentioning
confidence: 93%
“…The in vitro production of the T. solium metacestode excretion/secretion proteins from Peru and Zambia at 24h and 48h and the generation of line spectra mzXML files have been previously described [6]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations